The handbook of Alzheimer's disease and other dementias - Budson, Andrew E.; Kowall, Neil W. (Chichester, West Sussex, UK ; Malden, Mass. : Wiley-Blackwell, 2011)
"The reference is a broad-ranging review of Alzheimer's disease and other dementias from both basic and clinical neuroscience perspectives; it provides scientists and medical professionals with an extensive introduction and an up-to-date review of cutting-edge scientific advances. Brings the reader up-to-date with cutting-edge developments in this exciting and fast-paced field -- Summarizes the most recent developments in the fields of Alzheimer's disease and dementia -- Brings together articles from a prominent and international group of contributors -- Encompasses a unique range of topics, combining basic molecular perspectives and cognitive neurosciences."--Provided by publisher.
Alzheimer's disease / by Alan M. Mandell and Robert C. Green -- Vascular dementia / by Angela L. Jefferson, Amanda M. Gentile, and Ravi Kahlon -- Dementia with Lewy bodies / by Tamara G. Fong and Daniel Press -- Frontotemporal dementia / by Adam L. Boxer -- Other causes of dementia / by Peter Morin -- Genetic risk factors for dementia / by Paul Hollingworth and Julie Williams -- The neuropathology of the dementing disorders / by Ann C McKee and Brandon E. Gavett -- Amyloid beta peptide and the amyloid cascade hypothesis / by Carmela R. Abraham -- Other mechanisms of neurodegeneration / by Marina Boziki, Vassilis Papaliagkas, and MagdaTsolaki -- Rational therapeutics in dementia / by Neil W. Kowall -- Memory systems in dementia / by Andrew E. Budson -- Language processing in dementia / by Jamie Reilly, Joshua Troche, and Murray Grossman -- Executive functioning in dementia / by Robert A. Stern, Stacy L. Andersen, and Brandon E. Gavett -- Emotion and behavior in Alzheimer's disease and other dementias / by Christopher I. Wright -- Visuospatial function in Alzheimer's disease and related disorders / by Alice Cronin-Golomb -- Sleep and circadian rhythms in dementia / by David G. Harper -- Glimpses of the living brain with Alzheimer's disease / by Ronald J. Killiany -- Functional MRI in Alzheimer's disease and other dementias / by Maija Pihlajamäki & Reisa A. Sperling -- Molecular neuroimaging of the dementias: from scientific insights to clinical applications / by Bradford C. Dickerson -- Using EEG and MEG to understand brain physiology in Alzheimer's disease and related dementias / by Brandon A. Ally.
Includes bibliographical references and index.
Print version record.
Keywords: Alzheimer's disease; Dementia; Dementia; HEALTH & FITNESS -- Diseases -- Alzheimer's & Dementia; MEDICAL -- Neurology; Alzheimer's disease; Dementia; Dementie; Ziekte van Alzheimer; Electronic books; Handboeken (vorm); Elektronische boeken